1972
DOI: 10.2307/2037914
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Nuclear Spaces in Products of an Arbitrary Banach Space

Abstract: Abstract.It is proved that if E is an arbitrary nuclear space and F is an arbitrary infinite-dimensional Banach space, then there exists a fundamental (basic) system V of balanced, convex neighborhoods of zero for E such that, for each Kin i*~, the normed space Ev is isomorphic to a subspace of F. The result for F=lv (1 ^/>^oo) was proved by A. Grothendieck. (i) A locally convex space is nuclear if and only if it is isomorphic to a subspace of a product space (s)1, where / is an indexing set and (s) is the Fré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…An old and well-known result of Saxon [10] and Valdivia [15] states that every nuclear space embeds as a subspace of a suitable product of an arbitrarily given infinite-dimensional Banach space. On the other hand, Bellenot [1] showed that not all Schwartz spaces can be embedded into powers of l p for p > 1.…”
Section: Introductionmentioning
confidence: 99%
“…An old and well-known result of Saxon [10] and Valdivia [15] states that every nuclear space embeds as a subspace of a suitable product of an arbitrarily given infinite-dimensional Banach space. On the other hand, Bellenot [1] showed that not all Schwartz spaces can be embedded into powers of l p for p > 1.…”
Section: Introductionmentioning
confidence: 99%
“…n If E is the nuclear space s of rapidly decreasing sequences and F is any infinitedimensional Banach space with Schauder basis, then for every 0-neighborhood U in E there exists an absolutely convex 0-neighborhood Vc U in E such that /~v is norm-isomorphic to F (see [6]). This result of Saxon was improved later on by Valdivia [8] proving its validity when E is an arbitrary nuclear space and F any infinite-dimensional separable Banach space.…”
Section: O Introductionmentioning
confidence: 99%
“…
Abstract.Every Schwartz space is embeddable into some sufficiently high power E' of a given Banach space E if and only if E contains /"°°u niformly.In [13] Saxon showed that every nuclear space can be embedded in some sufficiently high power of every Banach space. In [2] Diestel and Lohman showed that a locally convex space that is embeddable in some sufficiently high power of every Banach space is a Schwartz space.
…”
mentioning
confidence: 99%